First record of Pyrgotidae (Diptera, Tephritoidea) from Uruguay with two new synonyms in the genus Leptopyrgota Hendel - Mello, Ramon Luciano (Papéis Avulsos de Zoologia, 2024)
Pyrgotidae are a small family of Tephritoidea of worldwide distribution, whose larvae are known to be endoparasites in the abdomen of adult Scarabaeidae beetles. This study presents the first record of the family from Uruguay, represented by the Leptopyrgota albitarsis Aczél, 1956 from Treinta y Tres, Quebrada de los Cuervos. Based on the study of holotypes, the following synonymy is proposed: Leptopyrgota albitarsis Aczél, 1956 = Leptopyrgota definienda Bernardi, 1991, new synonym and L. liae Bernardi, 1991 new synonym. Photos of the holotypes of the three studied species are presented, for the first time.